Consumption - Hudson, Ian 1979-; Hudson, Mark 1971- (polity, 2021)
"A crystal-clear guide to how consumption greases the wheels of modern capitalism"--
Keywords: Consumption (Economics); Capitalism; Privater Verbrauch; Konsumtheorie; Verbrauchermarkt